The Influence of Forensic Audits, Internal Audits, Information Technology, Auditor Attitudes and Professional Skepticism on Fraud Disclosure - Winda Utami Br Siburian; Auna Syafitri; Rahelsa Octaviana; Handriyani Dwilita (International Forum of Researchers and Lecturers, 2025)
This article examines the influence of Forensic Audit, Internal Audit, Information Technology, Auditor Attitude, and professional skepticism on Fraud Disclosure. The goal is to make a hypothesis about the influence of each variable that will be used in future research. The results of this article are: Forensic Accounting, Internal Audit, Information Technology, Auditor Attitude, and professional skepticism affect Fraud Disclosure.